Use of complementary and alternative medicine within Norwegian hospitals - Jacobsen, R (BMC Complement Altern Med, 2015)
BACKGROUND: Over the recent decades complementary and alternative medicine (CAM) use within and outside of the public health care system in Norway has increased. The aim of this study is to describe to what extent CAM is offered in Norwegian hospitals in 2013 and investigate possible changes since 2008. METHODS: In January 2013 a one-page questionnaire was sent to the medical director of all included hospitals (n = 80). He/she was asked to report whether or not one or more specific CAM therapies were offered in the hospital. Fifty-nine (73.8 %) hospitals responded and form the basis for the analyses. RESULTS: CAM was offered in 64.4 % of the responding hospitals. No major differences were found between public and private, or between somatic and psychiatric, hospitals. Acupuncture was the most frequent CAM method offered, followed by art- and expression therapy and massage. The proportion of hospitals offering CAM has increased from 50.5 % in 2008 to 64.4 % in 2013 (p = 0.089). The largest increase was found in psychiatric hospitals where 76.5 % of hospitals offered CAM in 2013 compared to 28.6 % in 2008 (p = 0.003). A small decrease was found in the proportion of hospitals offering acupuncture between 2008 (41.4 %) and 2013 (37.3 %). CONCLUSIONS: A majority of Norwegian hospitals offer some sort of CAM. The largest increase since 2008 was found in psychiatric hospitals. Psychiatric hospitals seem to have established a practice of offering CAM to their patients similar to the practice in somatic hospitals. This could indicate a shift in the attitude with regard to CAM in psychiatric hospitals.